Pengaruh Model Student Centered Learning (SCL) terhadap Motivasi Belajar Siswa Kelas VII - Gito Perdana; Suhirman Suhirman; Salamah Salamah; Rossi Delta Fitrianah (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This study aims to determine the effect of applying the Student Centered Learning (SCL) model on the learning motivation of seventh-grade students at SMPN 21 Bengkulu City. The background of this research is the low learning motivation of students, indicated by passive behavior, lack of initiative, and low enthusiasm during lessons.This research uses a quantitative approach with a quasi-experimental method and a non-equivalent pretest–posttest control group design. The sample consisted of 62 students divided into an experimental class (using SCL) and a control class (using conventional methods). The research instrument was a learning motivation questionnaire tested for validity and reliability, with a Cronbach’s Alpha value of 0.87.The results showed a significant increase in the experimental class, from an average pretest score of 68.45 to a posttest score of 82.13. Meanwhile, the control class increased only from 67.98 to 71.24. A simple linear regression test produced a significance value of 0.017 (< 0.05), indicating a positive and significant effect of SCL on students’ learning motivation.The study concludes that SCL effectively enhances both intrinsic and extrinsic learning motivation. Students become more diligent, more interested in learning, more independent, and more achievement-oriented. Therefore, teachers are recommended to apply student-centered learning more frequently.